2019
DOI: 10.1158/0008-5472.can-18-1010
|View full text |Cite
|
Sign up to set email alerts
|

MTAP Loss Promotes Stemness in Glioblastoma and Confers Unique Susceptibility to Purine Starvation

Abstract: Homozygous deletion of methylthioadenosine phosphorylase (MTAP) is one of the most frequent genetic alterations in glioblastoma (GBM), but its pathologic consequences remain unclear. In this study, we report that loss of MTAP results in profound epigenetic reprogramming characterized by hypomethylation of PROM1/CD133-associated stem cell regulatory pathways. MTAP deficiency promotes glioma stem-like cell (GSC) formation with increased expression of PROM1/ CD133 and enhanced tumorigenicity of GBM cells and is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 53 publications
1
45
4
Order By: Relevance
“…By analyzing the TCGA-GBM dataset, we also observed that deletion, rather than MTAP promoter methylation, is associated with MTAP mRNA expression. Our results contrast with a recent study that found a significant association of MTAP methylation with gene expression [40]. However, Hansen et al observed a very low coefficient of determination (R2) (0.19) with a low correlation coefficient (R) value (0.44) clearly below the values considered as strong correlation (>0.6); therefore, caution should be taken in interpreting the reported correlation between DNA promoter methylation and MTAP expression described [40].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…By analyzing the TCGA-GBM dataset, we also observed that deletion, rather than MTAP promoter methylation, is associated with MTAP mRNA expression. Our results contrast with a recent study that found a significant association of MTAP methylation with gene expression [40]. However, Hansen et al observed a very low coefficient of determination (R2) (0.19) with a low correlation coefficient (R) value (0.44) clearly below the values considered as strong correlation (>0.6); therefore, caution should be taken in interpreting the reported correlation between DNA promoter methylation and MTAP expression described [40].…”
Section: Discussioncontrasting
confidence: 99%
“…Metabolic changes in tumors, especially those relating to polyamines metabolism, demonstrate that many mechanisms underlying MTAP function need to still be clarified [35,36]. In gliomas, loss of MTAP locus is also frequently reported [37][38][39][40][41]. Nevertheless, the clinical and the biological impacts of MTAP are poorly explored in gliomas [37,38,42].…”
Section: Introductionmentioning
confidence: 99%
“…We found that in MTAP-deficient cells, gH2AX induction was delayed and weakened, yet extended, consistent with a compromised DDR and an attenuated capacity to resolve the DNA damage . Indeed, we observed a reduced basal level of total H2AX protein upon MTAP inhibition or MTAP knockout in GBM cell lines and in a transformed human astrocyte model (Hansen et al, 2019;Li et al, 2016) (Figures 1D, 1E, 1G-1I, 2A, and 2B). Chromatin fractionation experiments revealed this effect of MTAP loss in both chromatin-associated and chromatin-free H2AX fractions ( Figure 2C).…”
Section: Resultsmentioning
confidence: 66%
“…Glioblastoma cell lines including U251MG, T98G, and U138MG (all male cell lines; U251MG was described in Hansen et al, 2019), and T98G and U138MG were gifts from Dr. Darell D. Bigner) were cultured in Dulbecco's Modified Eagle's medium (GIBCO # 11995-065), supplemented with 10% (v/v) fetal bovine serum (FBS; Corning cat #35-010-CV). Normal human astrocytes (Lonza, Clonetics NHA, cat# CC-2565) were transformed by following previously described procedure to obtain a transformed cell line (OMRP) (Hansen et al, 2019;Li et al, 2016). GBM patient-derived cell line (#13-0302, described in Hansen et al, 2019) and the OMRP cell line were cultured in Neural Stem Cell medium (STEMCELL, cat# 05751) supplemented with EGF, FGF and heparin (20 ng, 10 ng, and 2 mg per ml, respectively).…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation